Evaluation of the stigmatizing attitudes of university students in front of people with mental disorders (Research, Society and Development, 2022)
The stigma related to mental disorders is considered a dimension to be valued and corresponds to a negative perception, resulting from anticipated judgments or erroneous knowledge. Thus, this research aimed to evaluate the attitudes of academics from eight health courses towards people with mental disorders. It is a transversal and quantitative research, with descriptive and analytical approaches. Data collection was carried out at a Federal University in northeastern Brazil, through the application of a semi-structured questionnaire and a scale validated by the Attribution Questionnaire - AQ27. In addition, it was approved by the Research Ethics Committee. The sample consisted of 328 students, 52.1% from the first cycle and 47.9% from the last cycle and 75.6% stated that they had not taken a mental health course. Regarding the AQ27, he observed scores of moderate to low stigma and some courses stood out, such as Occupational Therapy with less stigmatizing attitudes and Speech Therapy with the highest. Most of the students were from the first cycle and from Physiotherapy. In addition, stigmatization was present in most courses. Therefore, it can be inferred that stigma is related to several aspects, mainly, with academic education constituting a barrier in the assistance of these future professionals.